PERLINDUNGAN HUKUM BAGI NASABAH BAITUL MAAL WA TAMWIL (BMT) YANG DILIKUIDASI DI INDONESIA - Ma’shum, Syafi’atul Mir’ah (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
Baitul Maal wa Tamwil (BMT) is one type of micro finance institution that uses sharia principles. The BMT contributes to a real small economic by providing financing and channeling of funds. But the problem arises when liquidation occurs on the BMT, which rules should be used as a rule to solve it. This paper discusses the legal protection for BMT customers who are liquidated in Indonesia. The aim is to explain how legal protection forms for customers and why this legal protection is necessary for customers. The analysis used is statute approach and a conceptual approach. The legal basis of protection for BMT customers is Law no. 1 of 2013 on Microfinance Institutions (LKM), particularly articles 24 and 25, which regulate the prevention of disputes or revocation of licenses. Article 26 states that the Financial Services Authority (OJK) provides a deposit service if it makes them lose. But if BMT incorporated in the form of cooperative (koperasi) the law that use as basis is Law No. 25 of 1992, especially article 54 on the settlement. Differences in this rule become one of the factors slow the settlement of the problem of BMT customers that liquidated. The government should provide clear rules regarding the institutional status of BMT, so that the settlement of client's legal protection becomes clear